Effect of Nanosilica and Nanophosphate Composition on Characteristics of Artificial Insemination Semen Storage Ampoules - I Karyasa; Enike Kusumawati (Nanochemistry Research)
The aim of this research was to determine the effect of nano silica and nano phosphate composition on characteristics of artificial insemination semen storage ampoules. The laboratory research used a factorial completely randomized design (CRD) consisting of two factors, namely the measurement day factor consisting of 21 treatments (day 1 to 21) and the measurement time factor consisting of two treatments (day and night), each repeated three times. The variables studied included temperature (oC), humidity (%), and water content (%). Nanostructure characterization was carried out using FTIR, XRD, SEM-EDX measurements. The nano silica gel from silica powder from rice husk ash resulted in particles with an average size of 23.65 ± 1.0 nm. These particles were homogeneous, containing only Si-O bonds, in the form of an amorphous SiO2 phase. The nano calcium phosphate was obtained from hydroxy apatite previously isolated from cattle bone waste. It had an average size of 43.39 ± 1.0 nm, was homogeneous, and contained Ca-O, P-O, P=O, O-H bonds, in the form of an amorphous phase Ca3(PO3)2. The calcium silicophosphate gels exhibited homogeneous particle sizes with an average size of 36.98 ± 1.0 nm of Si/P =1. Their particle sizes increased by decreasing Si/P values and decreased by increasing Si/P values significantly. These gels contained Ca-O, P-O, P=O, O-H, Si-O, Si-O-P bonds in the form of amorphous or glacial CaxSiPOy phases. Additionally, the nano silica gel demonstrated a sensitivity to absorb and release water from and to its surrounding environment.